IL-6 promotes PD-L1 expression in monocytes and macrophages by decreasing protein tyrosine phosphatase receptor type O expression in human hepatocellular carcinoma - Yang Liu; Hui Yang; Yun Chen; Wei Sun; Zhongyi Yan; Wenjie Zhang; Yongliang Yao; Runqiu Jiang (Journal for ImmunoTherapy of Cancer)
Background We have previously discovered a relationship between the low expression of protein tyrosine phosphatase, receptor type O (PTPRO) in tumor-infiltrating T cells and immunosuppression. The aim of the present study was to investigate the relationship between decreased PTPRO and increased programmed death ligand 1 (PD-L1) in both the peripheral monocytes and tumor-infiltrating macrophages of human hepatocellular carcinoma (HCC).Methods The expression and correlation of all the indices were explored in monocytes and tumor-infiltrating macrophages within both human and mice HCC. The mechanic regulations were studied by using both in vitro and in vivo studies.Results We found a significant decrease in PTPRO in HCC peripheral monocytes that was associated with increased PD-L1 expression in peripheral monocytes and tumor-associated macrophages (TAMs) in HCC. Monocyte PD-L1 and PTPRO therefore could serve as valuable prognostic indicators for post-surgery patients with HCC and were associated with increased T-cell exhaustion (Tim3+T cells). A depletion of PTPRO promoted PD-L1 secretion in both monocytes and macrophages through the JAK2/STAT1 and JAK2/STAT3/c-MYC pathways. Increased IL-6 expression was associated with activation of JAK2/STAT3/c-MYC and with decreased PTPRO expression through the STAT3/c-MYC/miR-25–3 p axis. Monocytes and TAMs showed significantly increased miR-25–3 p expression, which could target the 3′ untranslated region of PTPRO. The miR-25–3 p expression positively correlated with serum IL-6 levels, but inversely correlated with PTPRO in HCC monocytes. IL-6/STAT3/c-MYC activation enhanced in vitro miR-25–3 p transcription and decreased PTPRO, while further promoting PD-L1 secretion. Adoptive cell transfer of c-MYC/miR-25–3 p–modified monocytes promoted tumor growth by downregulating PTPRO and causing a PD-L1–induced immunosuppression in an orthotopic tumor transplantation model.Conclusions Increased serum IL-6 downregulated PTPRO expression in HCC monocytes and macrophages by activating STAT3/c-MYC/miR-25–3 p and by further enhancing PD-L1 expression through JAK2/STAT1 and JAK2/STAT3/c-MYC signaling.